Manufacturing process of PU square carpet

By synthesizing flame-retardant ultraviolet absorbers and preparing flame-retardant nylon fibers, combining EVA hot melt adhesive and non-woven fabrics, the structure of flame-retardant nylon layer-non-woven fabric layer-PU foam layer is formed, which solves the problem of PU carpets being easily turned yellow and not having flame retardant, and achieves good ultraviolet absorption and flame retardant effects.

CN119550664APending Publication Date: 2025-03-04WEIHAI SHANHUA HUABAO CARPET CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448622.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing PU carpets are easily yellowed by ultraviolet rays, and do not have flame retardant properties. The flame retardant is easily volatile, and the flame retardant properties are weakened after long-term use.

Method used

The flame-retardant ultraviolet absorber was synthesized through esterification reaction and Furis rearrangement reaction, and the flame-retardant nylon fiber was melt-spinned by melt-spinning of nylon slices and composite functional agents. Combined with EVA hot melt adhesive and nonwoven fabric, a structure of flame-retardant nylon layer-nonwoven fabric layer-PU foam layer was formed.

Benefits of technology

It achieves good UV absorption performance and flame retardancy of PU carpet, avoids aging problems caused by ultraviolet irradiation, and ensures long-term flame retardant effect, and is not affected by use time and water washing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a manufacturing process of a PU square carpet, and belongs to the technical field of flame-retardant carpets. The manufacturing process comprises the following steps: firstly, preparing a flame-retardant ultraviolet absorbent, mixing the ultraviolet absorbent with nylon slices, carrying out melt spinning, then preparing a carpet surface blank layer by using the flame-retardant nylon yarns, and finally, carrying out thermocuring treatment at different temperatures to solve the warping problem in the carpet manufacturing process. The finally prepared carpet has good ultraviolet ray absorption capability and flame retardant capability; the flame-retardant ultraviolet absorbent used in the PU square carpet manufacturing process has good ultraviolet absorption capacity and good stability and is insoluble in water, so that the flame-retardant ultraviolet absorbent can take effect for a long time, and the effect cannot be weakened due to maintenance and cleaning; besides, environment-friendly materials which are nontoxic and harmless to human bodies are adopted in the preparation process of the PU square carpet, internal flame-retardant components cannot volatilize, harmful gas is not generated during combustion, and the PU square carpet is harmless to the human bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame-retardant carpets, and in particular relates to a manufacturing process of PU square carpets. Background Art

[0002] PU carpet, also known as polyurethane (PU) carpet, is a new type of floor decoration material that combines modern technology with traditional carpet craftsmanship. The core material of PU carpet is polyurethane, which is formed by the reaction of isocyanate and polyol. PU material has excellent physical and mechanical properties, such as high elasticity, wear resistance, tear resistance and weather resistance. In PU carpet, the application of PU material is mainly reflected in the backing part of the carpet, that is, the soft backing of the PU foam layer. This backing not only improves the comfort of the carpet, but its unique material properties and production process make PU carpet have significant advantages in comfort, environmental protection, durability and other aspects. It is widely used in many fields such as office places, home environments, and commercial spaces.

[0003] In the prior art, the main disadvantage of PU carpets is that the PU material is easily affected by ultraviolet rays and tends to turn yellow when exposed to sunlight for a long time, which greatly affects the aesthetics of the carpet. This limits the use of PU carpets in environments with strong sunlight, such as exhibition hall carpets, shopping mall carpets and other fields. In addition, PU carpets are not flame retardant. In the prior art, flame retardants are added during the manufacturing process of PU carpets, but these flame retardants are easy to volatilize, so the flame retardancy of PU carpets will weaken with the extension of use time and it is difficult to be effective for a long time. Summary of the invention

[0004] The object of the present invention is to provide a manufacturing process of PU carpet tiles to solve the problems mentioned in the above background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The manufacturing process of PU carpet tiles includes the following steps: Step 1: Mix pyrogallol, phosphorus oxychloride, aluminum chloride and N-methyl-2-pyrrolidone in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at 85°C for 8h. After the reaction is completed, remove the solvent by rotary evaporation, and recrystallize the obtained solid to obtain intermediate 1; The reaction process is as follows:

[0006] Step 2: Mix 2,4,6-trihydroxybenzoic acid, thionyl chloride and N,N-dimethylformamide in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at 70-80°C for 4 hours. After the reaction is completed, rotary evaporation is performed to obtain intermediate 2; The reaction process is as follows:

[0007] Step 3: Mix intermediate 1, intermediate 2, aluminum chloride and tetrahydrofuran in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at 160°C for 3 hours. After the reaction is completed, wash with deionized water, separate the organic layer with a separatory funnel, and rotary evaporate the organic layer to obtain intermediate 3; The reaction process is as follows:

[0008] Step 4: Mix the intermediate 3, triethylamine and dioxane in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and add the carbon tetrachloride solution of diethyl phosphite to the three-necked flask with a high-pressure dropping pump under ice-water bath conditions. After the addition is completed, remove the ice-water bath, react at a temperature of 40°C for 4h, and after the reaction is completed, remove the solvent by rotary evaporation, and obtain a flame-retardant ultraviolet absorber after the solid is recrystallized; The reaction process is as follows:

[0009] Step 5: Evenly mix the nylon slices and the composite functional agent, then extrude and granulate them through a twin-screw extruder, and then melt-spin them through an FDY high-speed spinning machine to obtain a flame-retardant nylon fiber; Step 6: The flame-retardant nylon fiber is used to weave the carpet surface germ layer. After inkjet printing, EVA hot melt adhesive is coated on the back of the surface germ layer, which is covered on the non-woven fabric. After cutting and heating and curing, the flame-retardant nylon layer-non-woven fabric layer is obtained. Step 7: Coat EVA hot melt adhesive on the surface of the PU foam layer, and attach the flame retardant nylon layer-non-woven fabric layer obtained in the sixth step to the PU foam layer. After cutting, heat and cure to obtain a PU square carpet with a structure of flame retardant nylon layer-non-woven fabric layer-PU foam layer.

[0010] Furthermore, the amount ratio of pyrogallol, phosphorus oxychloride, aluminum chloride and N-methyl-2-pyrrolidone used in the first step is 0.1 mol: 0.1 mol: 0.3-0.5 g: 80-100 mL.

[0011] Furthermore, the amount ratio of 2,4,6-trihydroxybenzoic acid, thionyl chloride, and N,N-dimethylformamide used in the second step is 0.1 mol: 0.1-0.15 mol: 150-180 mL.

[0012] Furthermore, the usage ratio of intermediate 1, intermediate 2, aluminum chloride and tetrahydrofuran used in the third step is 0.08 mol: 0.08 mol: 12-15 g: 130-150 mL.

[0013] Furthermore, the carbon tetrachloride solution of diethyl phosphite in the fourth step is prepared by mixing diethyl phosphite and carbon tetrachloride in a mass ratio of 1.3:1.

[0014] Furthermore, the usage ratio of the intermediate 3, triethylamine, dioxane, and carbon tetrachloride solution of diethyl phosphite used in the fourth step is 0.03 mol: 0.18-0.03 mol: 60-80 mL: 7.3 g.

[0015] Furthermore, the temperature of melt spinning in the fifth step is set to 220-230°C in zone 1, 230-240°C in zone 2, 230-245°C in zone 3, and 235-245°C in zone 4.

[0016] Furthermore, in the fifth step, the drawing speed of the melt spinning is 5000-6000 m / min, and the drawing ratio is 3-4 times.

[0017] Furthermore, in the sixth step, the temperature condition for heating and curing the hot melt adhesive is 120-140°C.

[0018] Furthermore, in the seventh step, the temperature condition for heating and curing the hot melt adhesive is 140-150°C.

[0019] Beneficial effects of the present invention: The present invention uses pyrogallol and phosphorus oxychloride as reaction raw materials, performs an esterification reaction under the condition of aluminum chloride as a catalyst to obtain an intermediate 1, then uses 2,4,6-trihydroxybenzoic acid as a raw material and thionyl chloride as an acylating agent to perform an acylation reaction to obtain an intermediate 2, then uses intermediate 1 and intermediate 2 as raw materials, performs an esterification reaction, performs a Fries rearrangement reaction under the catalysis of aluminum chloride to obtain a hydroxyl ortho-ketone intermediate 3, and finally reacts intermediate 3 with diethyl phosphite under the action of triethylamine and carbon tetrachloride to obtain a flame retardant ultraviolet absorber; the commonly used ultraviolet absorbers in the prior art (taking 2,4-dihydroxybenzophenone as an example) have an action principle of forming an intramolecular hydrogen bond through a carbonyl group and a hydroxyl group ortho to the carbonyl group, and the hydrogen bond breaks when exposed to ultraviolet energy, so the stronger the intramolecular hydrogen bond, the stronger the ultraviolet absorption performance and the stronger the stability. The flame retardant UV absorber is a dibenzophenone structure with three hydroxyl groups at the adjacent positions of the carbonyl group. This structure can form a stronger intramolecular hydrogen bond and thus has better UV absorption capacity and stability. In addition, the flame retardant UV absorber of the present invention also has a double-ended phosphate structure. This structure can act in a coordinated manner and decompose when heated to generate a non-combustible carbonized layer. The formation of this carbonized layer can prevent further pyrolysis of the substrate on the one hand, and prevent the thermal decomposition products inside it from entering the gas phase to participate in the combustion process on the other hand. In addition, this structure will also release PO• free radicals at high temperatures. The PO• free radicals can capture the H• free radicals and OH• free radicals that promote combustion, terminate the chain reaction of combustion, and achieve a flame retardant effect. Moreover, the flame retardant UV absorber of the present invention is insoluble in water, not easy to volatilize, will not become invalid with extended use time or cleaning, and can be effective for a long time.

[0020] The present invention uses nylon slices and a composite functional agent to melt-mix and spin, and uses the prepared flame-retardant nylon fiber to make a flame-retardant nylon layer with a flame-retardant effect. Subsequently, the flame-retardant nylon layer is coated with hot-melt adhesive and then bonded to a non-woven fabric to obtain a flame-retardant nylon layer-non-woven fabric layer. Finally, the PU foam layer is coated with EVA hot-melt adhesive and then thermoset with the flame-retardant nylon layer-non-woven fabric layer to obtain a PU square carpet with a structure of a flame-retardant nylon layer-non-woven fabric layer-PU foam layer. The present invention uses different temperatures for thermosetting treatment during the preparation process, thereby solving the problem of warping caused by heat absorption and water expansion during the preparation process of the PU carpet in the prior art.

[0021] The PU square carpet of the present invention uses environmentally friendly materials that are non-toxic and harmless to the human body during the preparation process, and the internal flame retardant components will not volatilize, so there is no harm to human skin, and the PU square carpet of the present invention has good elasticity, is soft and comfortable. In addition, the PU square carpet of the present invention has good weather resistance, will not cause aging problems due to ultraviolet radiation, and the anti-ultraviolet ability and flame retardant ability are not affected by the use time and water washing, and can be widely used in shopping mall carpets, exhibition hall carpets, aircraft carpets and other fields. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A flame retardant antibacterial agent comprises the following preparation steps: Step 1: 0.1 mol of pyrogallol, 0.1 mol of phosphorus oxychloride, 0.3 g of aluminum chloride, and 80 mL of N-methyl-2-pyrrolidone were mixed in a container, stirred evenly, and reacted at 85°C for 8 hours. After the reaction, the solvent was removed by rotary evaporation, and the obtained solid was recrystallized to obtain intermediate 1; Step 2: 0.1 mol 2,4,6-trihydroxybenzoic acid, 0.1 mol thionyl chloride, and 150 mL N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at 70°C for 4 h. After the reaction was completed, the intermediate 2 was obtained by rotary evaporation; Step 3: 0.08 mol of intermediate 1, 0.08 mol of intermediate 2, 12 g of aluminum chloride and 130 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 160°C for 3 h. After the reaction, the mixture was washed with deionized water, and the organic layer was separated by a separatory funnel. The organic layer was rotary evaporated to obtain intermediate 3; Step 4: 0.03 mol of intermediate 3, 0.18 mol of triethylamine and 60 mL of dioxane are mixed in a container, stirred evenly, and then 7.3 g of a carbon tetrachloride solution of diethyl phosphite is added dropwise to a three-necked flask under an ice-water bath. After the addition is complete, the ice-water bath is removed, and the reaction is carried out at a temperature of 40° C. for 4 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the obtained solid is recrystallized to obtain the flame-retardant ultraviolet absorber, wherein the carbon tetrachloride solution of diethyl phosphite is prepared from diethyl phosphite and carbon tetrachloride in a mass ratio of 1.3:1.

[0025] Example 2

[0026] A flame retardant antibacterial agent comprises the following preparation steps: Step 1: 0.1 mol of pyrogallol, 0.1 mol of phosphorus oxychloride, 0.4 g of aluminum chloride, and 90 mL of N-methyl-2-pyrrolidone were mixed in a container, stirred evenly, and reacted at 85°C for 8 hours. After the reaction, the solvent was removed by rotary evaporation, and the obtained solid was recrystallized to obtain intermediate 1; Step 2: 0.1 mol 2,4,6-trihydroxybenzoic acid, 0.125 mol thionyl chloride, and 165 mL N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at 75°C for 4 h. After the reaction was completed, the intermediate 2 was obtained by rotary evaporation; Step 3: 0.08 mol of intermediate 1, 0.08 mol of intermediate 2, 13.5 g of aluminum chloride and 140 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 160°C for 3 h. After the reaction was completed, the mixture was washed with deionized water, and the organic layer was separated by a separatory funnel. The organic layer was rotary evaporated to obtain intermediate 3; Step 4: 0.03 mol of intermediate 3, 0.24 mol of triethylamine and 70 mL of dioxane are mixed in a container, stirred evenly, and then 7.3 g of a carbon tetrachloride solution of diethyl phosphite is added dropwise to a three-necked flask under an ice-water bath. After the addition is complete, the ice-water bath is removed, and the reaction is carried out at a temperature of 40° C. for 4 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the obtained solid is recrystallized to obtain the flame-retardant ultraviolet absorber, wherein the carbon tetrachloride solution of diethyl phosphite is prepared from diethyl phosphite and carbon tetrachloride in a mass ratio of 1.3:1.

[0027] Example 3

[0028] A flame retardant antibacterial agent comprises the following preparation steps: Step 1: 0.1 mol of pyrogallol, 0.1 mol of phosphorus oxychloride, 0.5 g of aluminum chloride, and 100 mL of N-methyl-2-pyrrolidone were mixed in a container, stirred evenly, and reacted at 85°C for 8 hours. After the reaction, the solvent was removed by rotary evaporation, and the obtained solid was recrystallized to obtain intermediate 1; Step 2: 0.1 mol 2,4,6-trihydroxybenzoic acid, 0.15 mol thionyl chloride, and 180 mL N,N-dimethylformamide were mixed in a container, stirred evenly, and reacted at 80°C for 4 h. After the reaction was completed, the intermediate 2 was obtained by rotary evaporation; Step 3: 0.08 mol of intermediate 1, 0.08 mol of intermediate 2, 15 g of aluminum chloride and 150 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 160°C for 3 h. After the reaction, the mixture was washed with deionized water, and the organic layer was separated by a separatory funnel. The organic layer was rotary evaporated to obtain intermediate 3; Step 4: 0.03 mol of intermediate 3, 0.3 mol of triethylamine and 80 mL of dioxane are mixed in a container, stirred evenly, and then 7.3 g of a carbon tetrachloride solution of diethyl phosphite is added dropwise to a three-necked flask under an ice-water bath. After the addition is complete, the ice-water bath is removed, and the reaction is carried out at a temperature of 40° C. for 4 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the obtained solid is recrystallized to obtain the flame-retardant ultraviolet absorber, wherein the carbon tetrachloride solution of diethyl phosphite is prepared from diethyl phosphite and carbon tetrachloride in a mass ratio of 1.3:1.

[0029] Comparative Example 1 This comparative example is a UV absorber sold by Dongguan Kangjin Chemical New Materials Co., Ltd.

[0030] The flame retardant and antibacterial agent obtained in Examples 1-3 and the ultraviolet absorber sold by Dongguan Kangjin Chemical New Materials Co., Ltd. in Comparative Example 1 were respectively doped in epoxy resin at a solid content of 0.5% to prepare films, and the epoxy resin film without any other modifier was used as a blank control. The four films were subjected to ultraviolet aging test under the conditions of 4h ultraviolet irradiation at a test box temperature of 80°C, wherein the test wavelength of the ultraviolet light was QUVB (280-320nm) and the intensity was 0.81W / m 2 The yellowing value standard is tested according to the national standard GB11186.3-89. The test results are shown in Table 1: Table 1

[0031] It can be seen from Table 1 that the yellowness value of the epoxy resin film doped with the flame retardant ultraviolet absorber of the present invention is much lower than that of the epoxy resin film doped with the commercially available ultraviolet absorber, indicating that the flame retardant ultraviolet absorber of the present invention has a much stronger ability to absorb ultraviolet light than the commercially available ultraviolet absorber.

[0032] Example 4

[0033] A manufacturing process of a PU carpet tile comprises the following steps: The first step is to uniformly mix the nylon slices and the composite functional agent obtained in Example 1, and then extrude and granulate them through a twin-screw extruder, and then melt-spin them through an FDY high-speed spinning machine to obtain a flame-retardant nylon fiber, wherein the melt spinning temperature is set to 220° C. in the first zone, 230° C. in the second zone, 230° C. in the third zone, and 235° C. in the fourth zone; the drawing speed is set to 5000 m / min, and the drafting ratio is 3 times; Step 2: The flame retardant nylon fiber is used to weave the carpet surface germ layer. After inkjet printing, EVA hot melt adhesive is coated on the back of the surface germ layer, which is covered on the non-woven fabric. After cutting, the flame retardant nylon layer-non-woven fabric layer is obtained by heating and curing at a temperature of 120°C. Step 3: Coat EVA hot melt adhesive on the surface of the PU foam layer, and attach the flame retardant nylon layer-non-woven fabric layer obtained in the sixth step to the PU foam layer. After cutting, heat and cure at a temperature of 140°C to obtain a PU square carpet with a structure of flame retardant nylon layer-non-woven fabric layer-PU foam layer.

[0034] Example 5

[0035] A manufacturing process of a PU carpet tile comprises the following steps: The first step is to uniformly mix the nylon slices and the composite functional agent obtained in Example 2, and then extrude and granulate them through a twin-screw extruder, and then melt-spin them through an FDY high-speed spinning machine to obtain a flame-retardant nylon fiber, wherein the melt spinning temperature is set to 225° C. in the first zone, 235° C. in the second zone, 237.5° C. in the third zone, and 240° C. in the fourth zone; the drawing speed is set to 5500 m / min, and the drafting ratio is 3.5 times; Step 2: The flame retardant nylon fiber is used to weave the carpet surface germ layer. After inkjet printing, EVA hot melt adhesive is coated on the back of the surface germ layer, which is covered on the non-woven fabric. After cutting, the flame retardant nylon layer-non-woven fabric layer is obtained by heating and curing at a temperature of 130°C. Step 3: Coat EVA hot melt adhesive on the surface of the PU foam layer, and attach the flame retardant nylon layer-non-woven fabric layer obtained in the sixth step to the PU foam layer. After cutting, heat and cure at a temperature of 145°C to obtain a PU square carpet with a structure of flame retardant nylon layer-non-woven fabric layer-PU foam layer.

[0036] Example 6

[0037] A manufacturing process of a PU carpet tile comprises the following steps: The first step is to uniformly mix the nylon slices and the composite functional agent obtained in Example 3, and then extrude and granulate them through a twin-screw extruder, and then melt-spin them through an FDY high-speed spinning machine to obtain a flame-retardant nylon fiber, wherein the melt spinning temperature is set to 230° C. in the first zone, 240° C. in the second zone, 245° C. in the third zone, and 245° C. in the fourth zone; the drawing speed is set to 6000 m / min, and the drafting ratio is 4 times; Step 2: The flame retardant nylon fiber is used to weave the carpet surface germ layer. After inkjet printing, EVA hot melt adhesive is coated on the back of the surface germ layer, which is covered on the non-woven fabric. After cutting, it is heated and cured at a temperature of 140°C to obtain a flame retardant nylon layer-non-woven fabric layer; Step 3: Coat EVA hot melt adhesive on the surface of the PU foam layer, and attach the flame retardant nylon layer-non-woven fabric layer obtained in the sixth step to the PU foam layer. After cutting, heat and cure at a temperature of 150°C to obtain a PU square carpet with a structure of flame retardant nylon layer-non-woven fabric layer-PU foam layer.

[0038] Comparative Example 2 This comparative example is a flame retardant and sound insulation printed carpet sold by Foshan Dishemei Carpet Co., Ltd.

[0039] Comparative Example 3 The flame retardant ultraviolet absorber obtained in Example 3 used in the first step of Example 6 was removed, and the rest of the preparation process remained unchanged.

[0040] The PU square carpets prepared in Examples 4-6 and Comparative Example 2 and the flame retardant and soundproof printed carpet sold by Foshan Dishemei Carpet Co., Ltd. in Comparative Example 2 were tested for their combustion performance at a 45° inclination angle using GB / T14768-1993. The test results are shown in Table 2:

[0041] It can be seen from Table 2 that the PU square carpets of the present invention can generally achieve a flame retardant effect of the V-1 level, which is better than the commercially available carpets in Comparative Example 2, while the PU square carpets in Comparative Example 3 do not have a flame retardant effect because the flame retardant ultraviolet absorber of the present invention is not added. In summary, the addition of the flame retardant ultraviolet absorber of the present invention can give the PU square carpets good flame retardancy and ultraviolet absorption properties, so they can be widely used in shopping malls, subways, exhibition halls, subways, airplane carpets and other fields.

[0042] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. The manufacturing process of PU carpet tiles includes the following steps: Step 1: Mix pyrogallol, phosphorus oxychloride, aluminum chloride and N-methyl-2-pyrrolidone in a container and react at 85°C for 8h to obtain intermediate 1; Step 2: Mix 2,4,6-trihydroxybenzoic acid, thionyl chloride and N,N-dimethylformamide in a container and react at 70-80°C for 4 hours to obtain intermediate 2; Step 3: Mix intermediate 1, intermediate 2, aluminum chloride and tetrahydrofuran in a container, and react at 160°C for 3h to obtain intermediate 3; Step 4: Mix the intermediate 3, triethylamine and dioxane in a container, add a carbon tetrachloride solution of diethyl phosphite into the container under ice-water bath conditions, then remove the ice-water bath, and react at a temperature of 40° C. for 4 hours to obtain a flame-retardant ultraviolet absorber; Step 5: Evenly mix the nylon slices and the composite functional agent, then extrude and granulate them through a twin-screw extruder, and then melt-spin them through an FDY high-speed spinning machine to obtain a flame-retardant nylon fiber; Step 6: The flame-retardant nylon fiber is used to weave the carpet surface germ layer. After inkjet printing, EVA hot melt adhesive is coated on the back of the surface germ layer, which is covered on the non-woven fabric. After cutting and heating and curing, the flame-retardant nylon layer-non-woven fabric layer is obtained. Step 7: Coat EVA hot melt adhesive on the surface of the PU foam layer, and attach the flame retardant nylon layer-non-woven fabric layer obtained in the sixth step to the PU foam layer. After cutting, heat and cure to obtain a PU square carpet with a structure of flame retardant nylon layer-non-woven fabric layer-PU foam layer.

2. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: The amount ratio of pyrogallol, phosphorus oxychloride, aluminum chloride and N-methyl-2-pyrrolidone used in the first step is 0.1 mol: 0.1 mol: 0.3-0.5 g: 80-100 mL.

3. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: The amount ratio of 2,4,6-trihydroxybenzoic acid, thionyl chloride and N,N-dimethylformamide used in the second step is 0.1 mol: 0.1-0.15 mol: 150-180 mL.

4. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: The usage ratio of intermediate 1, intermediate 2, aluminum chloride and tetrahydrofuran used in the third step is 0.08 mol: 0.08 mol: 12-15 g: 130-150 mL.

5. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: The carbon tetrachloride solution of diethyl phosphite in the fourth step is prepared from diethyl phosphite and carbon tetrachloride in a mass ratio of 1.3:

1.

6. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: The usage ratio of the intermediate 3, triethylamine, dioxane and carbon tetrachloride solution of diethyl phosphite used in the fourth step is 0.03 mol: 0.18-0.03 mol: 60-80 mL: 7.3 g.

7. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: In the fifth step, the temperature of melt spinning is set to 220-230°C in zone 1, 230-240°C in zone 2, 230-245°C in zone 3, and 235-245°C in zone 4.

8. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: In the fifth step, the drawing speed of the melt spinning is 5000-6000 m / min, and the drawing ratio is 3-4 times.

9. The manufacturing process of the PU carpet tile according to claim 1, characterized in that: In the sixth step, the temperature condition for the hot melt adhesive to be heated and cured is 120-140°C.

10. The manufacturing process of PU carpet tiles according to claim 1, characterized in that: In the seventh step, the temperature condition for the hot melt adhesive to heat and cure is 140-150°C.